Influence of nitric acid treatment on the electrical conductivity in CNT fiber and CNT sheet - Muhammad Fairus Kamis (2014)
The background of carbon nanotube (CNT) is reviewed to provide a basic understanding on CNT. Although individual CNTs possess exceptional electrical properties, the understanding of the electrical properties of their assemblies is still unclear as these properties are greatly influenced by assembly structure and the functionalization of CNTs.